Adjusting the size of multicompartmental containers made of anionic liposomes and polycations by introducing branching and PEO moieties. (14th July 2017) - Pinguet, C.E.; Hoffmann, J.M.; Steinschulte, A.A.; Sybachin, A.; Rahimi, K.; Wöll, D.; Yaroslavov, A.; Richtering, W.; Plamper, F.A.
Abstract: We propose a strategy to adjust the size of multiliposomal complexes made of small unilamellar anionic liposomes (lipid bilayer vesicles prepared from zwitterionic lipid 1, 2-dioleoyl- sn -glycero-3-phosphocholine DOPC and ionic lipid 1-palmitoyl-2-oleoyl- sn -glycero-3-phospho-l -serine POPS with a typical diameter of 50 nm) with cationic polymers due to electrostatic attraction. Hereby, the use of quaternized poly(dimethylaminoethyl methacrylate), q PDMAEMA, allows the construction of multicompartmental carriers. Variation of the architecture and composition of various q PDMAEMA samples demonstrates the effect of introducing poly(ethylene oxide) PEO moieties and/or branching on the size of the hierarchical assemblies: both the PEO block (as seen for block copolymers and miktoarm stars) and the branching (as seen for star-shaped homopolymers and miktoarm stars) lead to smaller complexes compared to complexes with a linear q PDMAEMA homopolymer. Besides the use of cryogenic transmission electron microscopy (cryo-TEM), the formation of multicompartmental carriers composed of differently loaded liposomes is verified by two-color fluorescence cross-correlation spectroscopy (FCCS). Graphical abstract: Highlights: Size of complexes among anionic liposomes and cationic polymers can be adjusted. Use of copolymers with soluble/non-ionic chains decreases the size of complexes. Use of branched polymers further decreases the size of complexes. Joint transport of differently loaded liposomes is possible, as seen by FCCS.